ANALISIS SISTEM ADAPTASI DAN ETIKA LINGKUNGAN MASYARAKAT TERHADAP PERTAMBANGAN PASIR DI DESA SINAGAR - Ghina Raudatul Jannah; Exvina Nurazizah, Alviaziz Natasyah, Riska Yunita Sari, Hilmi Nugraha, Firza Ikshan Nugraha, Yani Sr (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Sukaratu sub-district is one of the sub-districts in Tasikmalaya Regency which is located close to the foot of Galunggung mountain. Therefore, there are several sand mines in Sukaratu Sub- district, especially in Sinagar Village. This mining empowers the community in Sinagar Village, so the sand mine certainly has an influence on the social system and environmental ethics of the village community. Community adaptation in Sinagar Village will be slightly different from the surrounding area. Thus the objectives of this research are: 1) Knowing the adaptation system of the Sinagar Village community related to sand mining, 2) Knowing the environmental ethics found in Sinagar Village in line with sand mining. The socio-economic and environmental conditions of the village community are affected by sand mining, including livelihoods, water quality, land conditions, and so on. In addition, sand distribution using large trucks often passes through village roads, resulting in damage. Thus, through this research, it is hoped that all parties can overcome social environmental problems due to mining.